Welfare words : critical social work & social policy - Garrett, Paul Michael, 1958- (Sage Publication, 2018)
Insightful and engaging, Welfare Words provides a critical analysis of social work and social policy in its articulation and discussion of a number of significant words and phrases. Written by an authoritative voice in the field, Paul Michael Garrett makes sense of complex theories which codify everyday experience, giving students and practitioners vital tools to better understand and change their social worlds. Lucid and accessible in style, Garrett offers an innovative approach to the study of Social Welfare, encouraging readers to think critically about the key issues in social work and social policy, including welfare dependency, social inclusion and exclusion, underclasses, anti-social behaviour, and more.